A Normative Legal Analysis of Crypto Assets as Collateral for Debt in Indonesia - Rilda Murniati Rilda; Muhamad Dafa Razwa Ramadhan (Universitas Lampung, 2025)
Cryptocurrency, or crypto assets, are virtual commodities emerging from technological advancements in commodity futures trading. To strengthen regulatory frameworks, it is essential to examine their characteristics as property, particularly their eligibility for property rights and use as collateral. This normative legal study employs a dogmatic approach, utilizing secondary data analyzed qualitatively. The findings indicate that crypto assets constitute intangible movable property with economic value, fulfilling property criteria in both Islamic and civil law. As such, property and ownership rights can be attached to crypto assets, allowing them to serve as collateral akin to shares. In cases of debtor default, execution through the sale of pledged crypto assets on an exchange is legally feasible.